Molecular orbital imaging for partially aligned molecules. (January 2017) - Qin, Meiyan; Zhu, Xiaosong
Abstract: We investigate molecular orbital reconstruction using high-order harmonic emissions from partially aligned molecular ensembles. By carrying out the reconstruction procedure using the harmonic sampling with or without the spectral minimum, the roles of the harmonic phase and amplitude modulation due to the partial alignment can be separately studied. It is found that with the prior knowledge of the orbital symmetry, the reconstructed result is very sensitive to the modulation of the harmonic phase for the π g orbital, while in the case of σ g orbital, the reconstructed result is mainly determined by the harmonic amplitude. These results can provide an important reference for the future experiment of molecular orbital imaging. Abstract : Highlights: Partial-alignment influence on molecular orbital imaging is investigated. The roles of the harmonic phase and amplitude modulation are studied separately. For πg orbital, the reconstructed result is sensitive to the harmonic phase. For σg orbital, the reconstructed result mainly depends on the harmonic amplitude.